2005
DOI: 10.1186/1742-2094-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Nicotinic acetylcholine (Ach) receptors are ligand-gated pentameric ion channels whose main function is to transmit signals for the neurotransmitter Ach in peripheral and central nervous system. However, the α7 nicotinic receptor has been recently found in several non-neuronal cells and described as an important regulator of cellular function. Nicotine and ACh have been recently reported to inhibit tumor necrosis factor-α (TNF-α) production in human macrophages as well as in mouse microglial cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(76 citation statements)
references
References 57 publications
4
72
0
Order By: Relevance
“…The mechanisms behind class-switching are still not fully known. Cholinergic signaling through α7 nicotinic acetylcholine receptor (α7nAChR) has been suggested to stimulate a shift to pro-resolving LM production [45]. The deficiency in cholinergic signaling in the AD brain is well known.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms behind class-switching are still not fully known. Cholinergic signaling through α7 nicotinic acetylcholine receptor (α7nAChR) has been suggested to stimulate a shift to pro-resolving LM production [45]. The deficiency in cholinergic signaling in the AD brain is well known.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that NRG1, through its binding to the ErbB receptors may increase the transcription of α7nAChRs in microglia. This would have interesting implications in the regulation of inflammation as previous work indicates that increases in α7nAChR expression can lead to a decrease in TNF-α, a known stimulator of inflammation [1,30]. Here we have documented ErbB expression in three immortalized cell lines and shown that NRG1 induces the phosphotyrosylation of the ErbB4 receptor in these cells.…”
Section: Discussionmentioning
confidence: 61%
“…This signal initiates the synthesis of ACh by the efferent arm of the vagus nerve. ACh then presumably acts on macrophages via the α7nAChR, thereby decreasing TNF-α release [1,8,30,38]. A similar cholinergic system has been described in the brain with microglia [15].…”
Section: Discussionmentioning
confidence: 99%
“…They also eliminate apoptotic cells during CNS remodeling and maturation. As in the peripheral immune system, recent data has demonstrated that the interaction of microglia with phosphatidylserine-expressing apoptotic neurons abrogates the inflammatory cascade and facilitates the elimination of damaged neurons through anti-inflammatory and neuroprotective processes [27]. Additionally, microglia produce neurotrophic molecules that promote neuronal survival and promote neuronal precursor cell proliferation, possibly through MAPK, PI3/AKT and delta-Notch signaling pathways [28].…”
Section: Immunological Approaches To Neuro-degenerative Disease Theramentioning
confidence: 97%